1982
DOI: 10.1002/j.1460-2075.1982.tb01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Distantly related sequences in the alpha- and beta-subunits of ATP synthase, myosin, kinases and other ATP-requiring enzymes and a common nucleotide binding fold.

Abstract: The a-and ,B-subunits of membrane-bound ATP synthase complex bind ATP and ADP: B contributes to catalyic sites, and a may be involved in regulation of ATP synthase activity. The sequences of ,B-subunits are highly conserved in Escherichia coli and bovine mitochondria. Also a and ( are weakly homologous to each other throughout most of their amino acid sequences, suggesting that they have common functions in catalysis. Related sequences in both a and (3 and in other enzymes that bind ATP or ADP in catalysis, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
3,315
3
25

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,092 publications
(3,399 citation statements)
references
References 52 publications
56
3,315
3
25
Order By: Relevance
“…SUR (TMD 0 -TMD-ABC-TMD-ABC), in addition to its unique property of association with a distinct protein subunit, Kir6.2, also contains an additional bundle of five TMDs (TMD 0 ), proposed to anchor SUR to the Kir6.2 channel pore [38]. Typical for ABCs, two highly conserved motifs, Walker A (GXXXXGKS/T) and Walker B (four hydrophobic residues followed by aspartate) frame a signature LSGGQ linker motif [39,40]. The crystal structure of homologous proteins indicates that the ε-amino acid and/or the main chain nitrogen of the invariant lysine of the Walker A motif participates in the binding of the β-and γ-phosphate of ATP whereas the Walker B aspartate coordinates Mg 2+ through hydrogen bonding to a water molecule [41].…”
Section: Sur Regulatory Module: Nucleotide Binding and Catalysismentioning
confidence: 99%
“…SUR (TMD 0 -TMD-ABC-TMD-ABC), in addition to its unique property of association with a distinct protein subunit, Kir6.2, also contains an additional bundle of five TMDs (TMD 0 ), proposed to anchor SUR to the Kir6.2 channel pore [38]. Typical for ABCs, two highly conserved motifs, Walker A (GXXXXGKS/T) and Walker B (four hydrophobic residues followed by aspartate) frame a signature LSGGQ linker motif [39,40]. The crystal structure of homologous proteins indicates that the ε-amino acid and/or the main chain nitrogen of the invariant lysine of the Walker A motif participates in the binding of the β-and γ-phosphate of ATP whereas the Walker B aspartate coordinates Mg 2+ through hydrogen bonding to a water molecule [41].…”
Section: Sur Regulatory Module: Nucleotide Binding and Catalysismentioning
confidence: 99%
“…A sequence element (Pro-Ala/Val-Ser-Asp-Asn) of unknown function is repeated ®ve times between positions 131 and 162. A putative Walker-type ATP binding site (ABS) was also found in the N-terminal region of the mAM protein (residues highlighted in Figure 1) (Walker et al, 1982).…”
Section: Isolation and Characterization Of The Full-length Mam Cdnamentioning
confidence: 99%
“…A Walker-type motif (Walker et al, 1982) re¯ecting the presence of a nucleotide-binding site was revealed by computer analysis of the mAM peptidic sequence. An in vitro assay showed that mAM exhibits an intrinsic ATPase activity and that the nucleotide-binding site is essential for this activity.…”
Section: Atpase Activity Of Mammentioning
confidence: 99%
“…Basically, there are three characteristic motifs found in all ABC-ATPases. The Walker A motif (blue) consists of the sequence GXXGXGKS/T where X represents any amino acid (Walker et al 1982). Together with the Walker B motif (red) (ΦΦΦΦD, where Φ is any hydrophobic residue), this motif forms the nucleotide binding fold of the P-loop ATPase family (Vetter and Wittinghofer 1999).…”
Section: Introductionmentioning
confidence: 99%